Official publishing : an overview : an international survey and review of the role, organisation and principles of official publishing - Cherns, Jack J. (Guides to official publications, 1979)
Official Publishing: An Overview is an international survey and review of the role, organization, and principles of official publishing. More specifically, it examines the organization, development, and effectiveness, including the economics, of state publishing as a means of communication between government and public, together with its relationship to the wider field of official information and communication activities. It also makes a broad comparison of the organization of publishing in the United Nations and its main agencies as well as some non-UN international organizations, particularl.